Implementation Of Productive Wakaf In Supporting Sharia-Based Economic Development In Urban Areas - Al Arif, Samsul (Management Science Doctoral Program, Pasundan University, 2023)
This study aims to analyze the implementation of productive waqf in supporting sharia-based economic development in urban areas. The main focus of the study is to understand the role and potential of productive waqf in driving the economy and improving the welfare of urban communities. This study also explores the challenges and opportunities faced in the management of productive waqf. The research method used is a qualitative approach with case studies in several waqf management institutions in urban areas of Indonesia. Data were collected through in-depth interviews, field observations, and document studies. This approach allows the study to explore comprehensive information regarding the implementation strategy and impact of productive waqf on the sharia economy. The results of the study indicate that productive waqf has a significant contribution to sharia-based economic development in urban areas. Productive waqf that is managed professionally is able to create jobs, increase access to social services, and provide public facilities such as education and health. However, the study also found obstacles, such as low waqf literacy in the community, limited manager capacity, and lack of regulatory support. The conclusion of this study is that the implementation of productive waqf has great potential to support sharia-based economic development in urban areas, as long as it is managed well and supported by adequate regulations. This study recommends increasing waqf literacy in the community, strengthening the capacity of management institutions, and collaborating with various parties to maximize the potential of productive waqf in creating sustainable socio-economic impacts.